2011
DOI: 10.1007/s00455-011-9326-4
|View full text |Cite
|
Sign up to set email alerts
|

Objective Assessment of Swallowing Function After Definitive Concurrent (Chemo)radiotherapy in Patients with Head and Neck Cancer

Abstract: The aim of this study was to objectively assess swallowing function and factors impacting it after curative intent definitive (chemo)radiotherapy (CRT) for head and neck squamous cell carcinoma (HNSCC). Swallowing function was studied in a cohort of 47 patients with locoregionally advanced (T1-4, N0-3) HNSCC treated with definitive CRT. Objective assessment of swallowing function was done using modified barium swallow (MBS) at baseline (pre-CRT) and subsequent follow-ups. Scoring of MBS was done using penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 26 publications
(42 reference statements)
2
67
1
4
Order By: Relevance
“…58 In contrast, studies that reported rates of symptomatic and asymptomatic aspiration with instrumental swallowing evaluations report higher aspiration rates of 30% to 62%. 59,60 Stricture An important contributor to dysphagia after CRT for HNC is pharyngoesophageal stricture. Stricture is not as common as physiologic impairments that reduce the range of motion of swallowing structures; however, when it develops it can greatly impact the swallowing function and lead to prolonged feeding tube dependence.…”
Section: Aspirationmentioning
confidence: 99%
“…58 In contrast, studies that reported rates of symptomatic and asymptomatic aspiration with instrumental swallowing evaluations report higher aspiration rates of 30% to 62%. 59,60 Stricture An important contributor to dysphagia after CRT for HNC is pharyngoesophageal stricture. Stricture is not as common as physiologic impairments that reduce the range of motion of swallowing structures; however, when it develops it can greatly impact the swallowing function and lead to prolonged feeding tube dependence.…”
Section: Aspirationmentioning
confidence: 99%
“…The dosimetric variables can be used to optimize radiotherapy treatment planning aiming at prevention of tube feeding dependence and to estimate the benefit of new radiation technologies. Head and neck cancer (HNC) can have a profound impact on swallowing function [1][2][3][4][5]. The treatment of these patients with radiotherapy (RT), chemoradiation (CRT) or radiotherapy plus cetuximab (CetRT) may further affect swallowing function, eventually leading to tube feeding dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Diese Tendenz untermauert auch eine Studie von Agarwal und Kollegen, die anhand einer Untersuchung von 47 Patienten mit einem fortgeschrittenen Tumor des Kopf-Hals-Bereiches, bei denen eine kurative Radiochemotherapie durchgeführt wurde. Ein modifi zierter Bariumschluck zeigte nach 6 Monaten eine signifi kante Verschlechterung des Schluckens mit Zunahme an pharyngealen Residuen aufgrund einer Bolustransportstörung sowie eine erhöhten Aspirationsneigung [ 32 ] . Neben Sensibilität-und Motilitätsstörungen ist hier auch eine postradiogen reduzierte Larynxelevation ursächlich.…”
Section: Neurogene Ursachenunclassified